Assessment of Readability Level of Reading Materials in Indonesia EFL Textbooks - Ika Apriani Fata; Endang Komariah; Andira Riski Alya (Lingua Cultura, 2022)
The research aimed to assess the readability of reading material in two different English textbooks published by different publishers. Many pieces of research have been conducted to examine the reading materials in English textbooks, and it had been discovered that the reading materials were insufficiently adequate for the levels of students. The research applied a descriptive content analysis method to analyze, interpret, and describe the data. The Flesch Reading Ease formula was as an instrument. The research’s data were derived from the English textbook “Pathway to English” by Erlangga grade X and the English textbook “Bahasa Inggris” by The Ministry of Education and Culture grade X. Based on the findings of the research, five reading texts out of 15 match with students’ level (fairly difficult level) of grade X in the first textbook, while three texts out of 13 equal with students’ level (fairly difficult level) of grade X in the second textbook. Furthermore, the first textbook’s average readability score indicates that the texts are ‘standard’, whereas the second textbook indicates that the texts are ‘fairly difficult’. Based on the study findings, some recommendations for teachers are to use the readability formulas to provide appropriate reading material for students, as well as for other researchers to conduct a larger context about readability.